1997
DOI: 10.1037/0096-1523.23.1.244
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements during parallel–serial visual search.

Abstract: Two experiments (one using O and Q-like stimuli and the other using colored-oriented bare) investigated the oculomotor behavior accompanying parallel-serial visual search. Eye movements were recorded as participants searched for a target in 5-or 17-item displays. Results indicated the presence of parallel-serial search dichotomies and 2:1 ratios of negative to positive slopes in the number of saccades initiated during both search tasks. This saccade number measure also correlated highly with search times, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
178
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(213 citation statements)
references
References 22 publications
30
178
2
Order By: Relevance
“…Contrary to the predictions of the no-guidance hypothesis, initial saccade latencies to novel distractors were not significantly shorter than those to old distractors [F(1,11) 0.07, n.s.]. And although we did find an increase in latency with set size [F(2,22) 6.92, p .01] (see also Zelinsky & Sheinberg, 1997) and an interaction between set size and novelty [F(2,22) 4.00, p .05], the direction of this interaction was opposite to that of the prediction: The latency difference between novel and old distractors increased with set size, with latencies to novel Eye-movement data. Our expectation was that search would be guided more efficiently to new distractors than to old ones and that familiar distractors would show an intermediate level of guidance.…”
Section: Methodscontrasting
confidence: 54%
See 2 more Smart Citations
“…Contrary to the predictions of the no-guidance hypothesis, initial saccade latencies to novel distractors were not significantly shorter than those to old distractors [F(1,11) 0.07, n.s.]. And although we did find an increase in latency with set size [F(2,22) 6.92, p .01] (see also Zelinsky & Sheinberg, 1997) and an interaction between set size and novelty [F(2,22) 4.00, p .05], the direction of this interaction was opposite to that of the prediction: The latency difference between novel and old distractors increased with set size, with latencies to novel Eye-movement data. Our expectation was that search would be guided more efficiently to new distractors than to old ones and that familiar distractors would show an intermediate level of guidance.…”
Section: Methodscontrasting
confidence: 54%
“…Conversely, search becomes less efficient as target-distractor similarity increases, presumably because these target-like distractors are competing more strongly with the actual target for attention (e.g., Duncan & Humphreys, 1989;Wolfe, 1994). More direct support for this relationship has come from studies of eye movements during search, which have shown that the likelihood of a distractor being fixated increases with the number of features that it shares with a target (D. E. Williams & Reingold, 2001;Zelinsky, 2008;Zelinsky & Sheinberg, 1997; see also L. G. Williams, 1966, for an early observation). In addition to generally supporting the role of target-related guidance in search, such analyses of distractor fixations also enable one to identify the target features that are most important for guidance (e.g., Motter & Belky, 1998;Pomplun, 2006;Rutishauser & Koch, 2007; see also Tatler, Baddeley, & Gilchrist, 2005).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Other researchers seem to assume that understanding eye movement behavior in visual search may not be particularly important. However, many studies (Binello, Mannen, & Ruddock, 1995;Findlay, 1995Findlay, , 1997Gilchrist, Findlay, & Heywood, in press;Gould, 1973;Miller, 1978;Motter & Belky, 1998aPonsoda, Scott, & Findlay, 1995;Previc, 1996;Scialfa & Joffe, 1998;Scialfa, Thomas, & Joffe, 1994;Scinto, Pillalamarri, & Karsh, 1986;Staller & Sekuler, 1980;Togami, 1984;Williams, Reingold, Moscovitch, & Behrmann, 1997;Zelinsky, 1996;Zelinsky, Rao, Hayhoe, & Ballard, 1997;Zelinsky & Sheinberg, 1997) have indicated that eye movement data yield important information about visual search. Indeed, Findlay and Gilchrist (1998) argued that the tradition to pay little attention to eye movements in search research is misguided, and they demonstrated that when viewers are free to move their eyes, no additional covert attentional scanning Occurs. Whereas most studies of eye movements during visual search have examined complex search tasks, some (Findlay, 1997;Ottes, Van Gisbergen, & Eggermont, 1985;Viviani & Swensson, 20 Recent studies by Jordan, Patching, and Milner (1998) and Patching and Jordan (in press) have demonstrated that when fixation location is not ensured by an eye-tracking system, central fixations occurred on only 23% of trials.…”
Section: Eye Movements and Visual Searchmentioning
confidence: 99%
“…These latter studies operate on the logic that because eye movement behavior parallels that of the underlying spatial attention [20,27,33,44,65,66] (but see [43] for a somewhat different view), studying the distribution of eye movements will reveal whether the attentional deficit is best characterized by a gradient or step function. A number of eye movement studies have already characterized the abnormal pattern in patients with neglect and have shown that these patients make fewer ipsilesional than contralesional saccades, are slower to initiate leftward saccades, make multiple small saccades to locate the contralateral target, have prolonged search times for ipsilesional targets and adopt a rightward (rather than leftward) position for starting their visual exploration [8, 15, 19, 30 32, 62].…”
Section: Introductionmentioning
confidence: 99%